2019
DOI: 10.1111/ddi.12956
|View full text |Cite
|
Sign up to set email alerts
|

Effects of altitude, land use and microsites on early life performance of a high mountain tree: Insights from an in situ sowing experiment

Abstract: Aim: Understanding the forces that drive range shifts in forest landscapes is imperative for predicting species distributions under anthropogenic climate and land use change. However, empirical studies exploring how these components jointly influence critical early life stages of mountain tree species across environmental gradients are scarce. We used the high mountain tree Polylepis australis as model species to investigate the relative importance of altitude and associated climatic conditions, land use for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…We believe this impacts species distribution. Studies elsewhere have also indicated that both facilitation and competition influence species persistence and elevation ranges (Olsen et al 2016, Ettinger and HilleRisLambers 2017, Cáceres et al 2019). For the tropics, these results are consistent with field observations along the same gradient (Muñoz Mazón et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We believe this impacts species distribution. Studies elsewhere have also indicated that both facilitation and competition influence species persistence and elevation ranges (Olsen et al 2016, Ettinger and HilleRisLambers 2017, Cáceres et al 2019). For the tropics, these results are consistent with field observations along the same gradient (Muñoz Mazón et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…One month before starting the field experiments (November 2015), grasses and herbs of all common gardens were cut to avoid initial differences in vegetation structure. By cutting the vegetation we also expected to mimic the herbaceous sites with low grazing pressure, where the highest P. australis recruitment is recorded (Figure 2(c-d)) [25,32,43]. Regeneration of this species within woodlands is severely reduced by litter, ferns and moss, and canopy cover [43][44][45][46].…”
Section: Experimental Designmentioning
confidence: 99%
“…Polylepis australis is dominant in highland woodlands of central Argentina mountains [20,21], where it is distributed from 900 to 2700 m a.s.l [22]. Previous studies found variation in the species regeneration traits, such as seedling growth and survival, along its elevation range [22][23][24][25]. In particular, these studies suggest optimal conditions for P. australis at midelevations, since its performance decreases towards both elevation extremes in response to the constraining factors typical of semi-arid mountain ecosystems [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation